Aspecto psicoafectivo de escolares víctimas de bullying y rendimiento académico. - Bohorquez Rogel, Dayana; Villavicencio Aguilar, Carmita; Guartan Duchitanga, July (My University, 2021)
This research aims to determine the characteristics of the psycho-affective aspect of schoolchildren who are victims of bullying, the degree of affectation and the consequences in their daily lives. The method was synthetic analytical, with a mixed approach, applying instruments such as: psychological interview, observation and Questionnaire on Bullying and Peer Abuse (CIMEI). The results showed the presence of bullying, the affectation of the emotional state of the victims, due to a disturbing school environment, which prohibits children from performing activities they like, poor ability to relate to others, lack of motivation to develop in the activities of the school context.
Esta investigación pretende determinar el aspecto psicoafectivo y el rendimiento académico de escolares víctimas de bullying, bajo el enfoque cognitivo – conductual, direccionado a la reestructuración de ideas irracionales y a la posibilidad de mejorar ciertas actitudes. La metodología utilizada fue mixta, aplicando instrumentos como: entrevista psicológica, observación y Cuestionario sobre Intimidación y Maltrato Entre Iguales (CIMEI). Los resultados evidenciaron la presencia de acoso escolar, la afectación del estado emocional de las víctimas, y los inconvenientes que presentan respecto a la respuesta académica, originando desmotivación de asistir a clases, y la disminución en su rendimiento escolar.
Keywords: BULLYING; VÍCTIMAS; ESTADO EMOCIONAL; RENDIMIENTO ESCOLAR